SOCIAL COGNITION ELEMENTS OF CRITICAL DISCOURSE ANALYSIS IN BARACK OBAMA’S SPEECH AT THE DEMOCRATIC NATIONAL CONVENTION 2020 - Fadhilah, Nurul; Yatmikasari, Ika; Listiani, Toneng (Universitas Islam Negeri Sunan Gunung Djati, 2022)
This paper employs one strand of Critical Discourse Analysis as a framework to discuss a discourse of political figures. It is a speech delivered by Barack Obama with regard to the issue of 46th president election in 2020 between Trump and Biden. That approach is van Dijk’s (1993) social cognition theory that is focused on the elements of social cognition contained in the speech. In line with Memon, et al. (2014) findings on analyzing Benazir Bhutto’s last speech, there are nine elements of social cognition. Meanwhile, the findings of current study show that there are three social cognition elements in the speech. They are social attachment, mind control, and glorification. In conclusion, social cognition can explore mental awareness of the scenario writer which then forms the text. Keywords: critical discourse analysis, social cognition, speech